Evaluation of the Effectiveness of Learning Aqidah Akhlak: (Evaluation Study of Learning Aqidah Akhlak through Lecture and Discussion Method) - Najamudin Najamudin; Surahman Hidayat (International Journal of Islamic Educational Research, 2025)
This article discusses the evaluation of the effectiveness of Aqidah Akhlak learning through a literature review that focuses on lecture and discussion methods. In learning Aqidah Akhlak, choosing the right method is the key to success in delivering material and shaping students' character. The lecture method is effective in conveying basic information in a systematic manner, while the discussion method emphasizes more on the active involvement of students and the development of critical thinking skills. This article examines various scientific literature to analyze the advantages, disadvantages, and relevance of these two methods in the learning of Aqidah Akhlak. The results of the study show that the use of both methods in an integrated manner can provide more optimal results, with lectures as an introduction and discussions as a deepening of the material. These findings provide a theoretical perspective for educators in designing effective learning strategies.